(untitled) (Scientific journal of the Fergana State University, 2024)
This article gives information about the scientific and creative path of the enlightened writer and public figure Sadriddin Aini as well as his effective works on the development of the press in Turkestan, in the expansion of scientific publications, in the creation of textbooks and manuals for new schools. Also, this article mentions Jadid schools in Bukhara. The problems of the organs have been scientifically analyzed as well in the given article.